2019
DOI: 10.15644/asc53/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Dental Treatment Under General Anesthesia in a Day Care Surgery Setting

Abstract: Objective To analyze data on full-mouth rehabilitation under general anesthesia (GA) performed at the University Clinical Hospital Zagreb with emphasis on patient characteristics, type of procedure and postoperative complications. Materials and methods Retrospective chart review of 100 patients treated under GA at the Dental clinic’s day care surgery. Patient’s demographic (sex, age) and clinical data (diagnosis, GA technique, intubation type, procedure duration, number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Special needs patients often have a reduced ability to perform oral hygiene themselves and access to dental services is reduced. This in turn can result in an increased risk of caries and periodontal disease [ 5 7 ]. This hypothesis is clearly reflected in the numbers of carious or unsustainable teeth in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special needs patients often have a reduced ability to perform oral hygiene themselves and access to dental services is reduced. This in turn can result in an increased risk of caries and periodontal disease [ 5 7 ]. This hypothesis is clearly reflected in the numbers of carious or unsustainable teeth in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This often leads to oral diseases (caries, periodontitis, etc. [ 5 7 ]), which increase the need for dental treatment [ 5 , 8 , 9 ]. In addition, people with intellectual disabilities are often unable to recognise dental problems and/or oral pain or discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Dental care is necessary to prevent and treat oral infections, cavities, and toothache. Poor oral hygiene is one of the public health problems which majorly affect children and patients with mental disorders and physical disabilities (21). Thus, there is now more emphasis on active surveillance and prevention of caries (1,22).…”
Section: Discussionmentioning
confidence: 99%
“…5 The rationale for GA in dental treatments is to allow complete oral rehabilitation, which includes pulpal treatment, extractions of non-restorable teeth, dental restorations, and/or stainless-steel crowns (SSCs) in a single session. 5 Lately there has been a trend towards fewer root treatments in primary teeth (pulpotomy/ pulpectomy) and more of extractions, SSCs, and fissure sealing of teeth under GA. 6 Most pediatric dental GA candidates are medically compromised children who are uncooperative but otherwise healthy children and children with early childhood caries. 6 This study included children aged from birth to 13 years indicated for full mouth rehabilitation who were otherwise healthy as well as medically compromised children.…”
Section: Introductionmentioning
confidence: 99%
“…5 Lately there has been a trend towards fewer root treatments in primary teeth (pulpotomy/ pulpectomy) and more of extractions, SSCs, and fissure sealing of teeth under GA. 6 Most pediatric dental GA candidates are medically compromised children who are uncooperative but otherwise healthy children and children with early childhood caries. 6 This study included children aged from birth to 13 years indicated for full mouth rehabilitation who were otherwise healthy as well as medically compromised children. These children were entitled for treatment by the Bahrain Defense Force (BDF) military.…”
Section: Introductionmentioning
confidence: 99%